Imprint of Initial Education and Loss of Ly49C/I in Activated Natural Killer Cells of TAP1-KO and C57BL/6 Wildtype Mice - Patil, Neha D.; Domingues, Olivia; Masquelier, Cécile; Theresine, Maud; Schlienger, Oceane; Njinju Amin Asaba, Clinton; Thomas, Marine; Seguin-Devaux, Carole; Slevogt, Hortense; Ollert, Markus; Zimmer, Jacques (Frontiers in Immunology, 2022)
Natural killer (NK) cells are important effectors of the innate immune system and participate in the first line of defense against infections and tumors. Prior to being functional, these lymphocytes must be educated or licensed through interactions of their major histocompatibility complex class I molecules with self-specific inhibitory receptors that recognize them. In the absence of such contacts, caused by either the lack of expression of the inhibitory receptors or a very low level of major histocompatibility complex class I (MHC class I) proteins, NK cells are hypo-reactive at baseline (ex vivo). After stimulation (assessed through plate-bound antibodies against activating receptors or culture in the presence of cytokines such as interleukin (IL)-2 or IL-15) however, they can become cytotoxic and produce cytokines. This is particularly the case in transporter associated with antigen processing (TAP)-deficient mice, which we investigated in the present study. Transporter associated with antigen processing transports endogenous peptides from the cytosol to the endoplasmic reticulum, where they are loaded on nascent MHC class I molecules, which then become stable and expressed at the cell surface. Consequently, TAP-KO mice have very low levels of MHC class I expression. We present a study about phenotypic and functional aspects of NK cells in two mouse strains, C57BL/6 wildtype and TAP1-KO in spleen and lung. We observed that in both types of mice, on the same genetic background, the initial pattern of education, conferred to the cells via the inhibitory receptors Ly49C/I and NKG2A, was maintained even after a strong stimulation by the cytokines interleukin-2, interleukin-12, interleukin-15 and interleukin-18. Furthermore, the percentages of activated NK cells expressing Ly49C/I and Ly49I were strongly down-modulated under these conditions. We completed our investigations with phenotypic studies of NK cells from these mice.